Trauma Psikososial Sebagai Faktor Dominan Skizofrenia Hasil Wawancara Dengan Pasien, Keluarga, Dan Tenaga Kesehatan - Sucipto, Ade; Rahayu, Sri; Supriatna, Yayat; Yustika, Priti (STIKES Borneo Cendekia Medika, 2025)
Background: Schizophrenia is a severe mental disorder characterized by hallucinations, delusions, and social dysfunction. While biological factors have been widely recognized in its etiology, emerging evidence highlights the significant role of psychosocial trauma. However, this aspect remains under-addressed in primary healthcare services. Objective: This study aimed to explore the psychosocial trauma experiences of individuals diagnosed with schizophrenia and to understand the perspectives of families and healthcare workers on the triggering factors within a community context. Methods: A qualitative case study approach was employed. Data were collected through in-depth interviews with 31 individuals diagnosed with schizophrenia, their family members, and healthcare providers in the working area of Sungai Rangit Public Health Center, Central Kalimantan. Thematic analysis was conducted following Braun and Clarke’s method. Results: Findings showed that 93.5% of participants had significant psychosocial trauma histories. The most common traumas included domestic violence, loss of significant others, bullying, romantic betrayal, and unresolved childhood trauma due to harsh parenting. Additional comorbid factors such as substance abuse and a history of seizures in infancy were also identified. Healthcare workers acknowledged that psychosocial aspects are often overlooked due to limited time, resources, and training. Families exhibited limited knowledge and persistent stigma toward mental illness. Conclusion: Psychosocial trauma is a dominant factor in the development of schizophrenia. A more comprehensive and trauma-informed approach is needed in primary care settings, including family education and training for healthcare professionals on early detection and psychosocial support.